BOAT The 'Retirement Dream' Trap: Why Most Men Who Buy a Boat After 60 Lose $200,000 Within 3 Years (2026)
Most men who buy a boat after 60 don't lose money because they made a mistake. They lose it because the financial architecture around boat ownership — broker commissions, operating cost escalation, a depreciation curve no one modelled, marina fee increases now driven by private equity, and an exit cost trap — is designed to extract from every point in the ownership cycle. This video dissects all five mechanisms with verified numbers, a named federal lawsuit, and the arithmetic any viewer can check independently.